Profil Dan Faktor Yang Mempengaruhi Keputusan Konsumen Mobil Toyota Yaris Di Manado - Waworuntu, Santi S (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
The aims of this research is to study consumer characteristics and the influence of promotion, price, product and place on consumer purchase decision of Toyota Yaris car at PT. Hasjrat Abadi Manado. The data is primary data collected from questionnaire of which distributed to 100 buyers as well as owners of Toyota Yaris car at PT. Hasjrat Abadi Manado. Data analysis result is obtained using cluster analysis and multiple linear regression analysis. The result of cluster analysis shows that there are three clusters: cluster 1 with lower middle-income buyers, cluster 2 with upper middle-income buyers, and cluster 3 with upper income buyers. The results of multiple linear regression analysis are: partial result on consumer decision with the correlation coefficient of promotion (X1) is 80.3%, price (X2) is 51.4%, product (X3) is 82.4%, and place (X4) is 62.4% which means these four variables have strong relationship on consumer decision, and simultaneously test result shows that promotion, price, product, and place contribute 74.5% with Fcount 69.373 and under 0.05 level of significance